Characterization and epidemiology of antimicrobial resistance patterns of Salmonella spp. and Staphylococcus spp. in free-ranging rhesus macaque (Macaca mulatta) at high-risk interfaces with people and livestock in Bangladesh - Rahman, Md. Kaisar; Hassan, Mohammad Mahmudul; Islam, Shariful; Rostal, Melinda K.; Uddin, Md. Helal; Hagan, Emily; Samad, Mohammed Abdus; Flora, Meerjady Sabrina; Epstein, Jonathan H.; Islam, Ariful (Frontiers in Veterinary Science, 2023)
Antimicrobial resistance (AMR) is a growing global health threat for humans and animals. Environmental contamination of antimicrobials from human and domestic animal feces has been linked to AMR in wildlife populations, including rhesus macaques. This study aimed to describe the eco-epidemiology of AMR within Salmonella and Staphylococcus species isolated from rhesus macaques. We followed macaque groups for four hours per day (two days) to observe the direct and indirect contact rate and type between macaques and people and livestock. We collected 399 freshly defecated, noninvasive fecal samples from macaques at seven sites in Bangladesh in January-June 2017. Bacterial isolation and identification were conducted using culture, biochemical characteristics, and polymerase chain reaction (PCR). An antimicrobial susceptibility test (AST) for 12 antimicrobials for each organism was conducted using the Kirby-Bauer disc diffusion method. The overall prevalence of Salmonella spp. and Staphylococcus spp. in rhesus macaques was 5% (n=18; 95% CI: 3-7%) and 16% (n=64; 95% CI: 13-20%), respectively. All the isolated Salmonella and most of the Staphylococcus spp. (95%; 61/64; 95% CI: 86.9-99%) were resistant to at least one antimicrobial. The odds of a fecal sample having antimicrobial-resistant Salmonella spp (OR=6.6; CI: 0.9-45.8, P=0.05) and Staphylococcus spp. (OR=5.6; CI: 1.2-26, P=0.02) were significantly higher in samples collected at peri-urban sites than those collected at rural and urban sites. Salmonella spp. were most frequently resistant to tetracycline (89%), azithromycin (83%), sulfamethoxazole-trimethoprim (50%), and nalidixic acid (44%). Staphylococcus spp. were found to be highly resistant to ampicillin (93%), methicillin (31%), clindamycin (26%), and rifampicin (18%). Both bacterial species produced colonies with multidrug resistance to up to seven antimicrobials. Direct and indirect contact rates (within 20m for at least 15 min) and resource sharing between macaques and people were higher in urban sites, while macaque-livestock contact rates were higher in rural sites. The study shows that resistant microorganisms are circulating in rhesus macaques, and direct and indirect contact with humans and livestock might expand the resistant organisms.